Exploring the Relationship between Religion, State, and Economy: A Global Study - Lestari Agusalim (KURAS Institute, 2025)
Religion plays a crucial role not only in shaping individual and group behavior but also in influencing governance structures and economic performance. Many countries incorporate religion into their constitutions, with some adopting official state religions as the foundation of governance, thereby creating theocratic states. This study aims to explore the relationship between religion and state governance, as well as the relationship between religion and economic performance, based on the classification of countries by religion. The data for this analysis is sourced from the World Bank and the Pew Research Center. It encompasses GDP per capita figures for 133 countries for the years 1990 and 2022, along with estimates of the global population by religion in 2050, derived through a cohort-component technique. A descriptive and comparative approach is utilized to explore the relationship between religion, governance, and the economic performance of these nations. This study finds that countries with an official state religion, supported by strong governance and prudent resource management, tend to achieve better economic outcomes, as evidenced by higher GDP per capita levels. Conversely, countries with weak governance or without clear religious support often experience economic stagnation. The findings recommend the importance of integrating religious values into inclusive and sustainable development policies.